Laccases: Production, Expression Regulation, and Applications in Pharmaceutical Biodegradation - Yang, Jie; Li, Wenjuan; Ng, Tzi Bun; Deng, Xiangzhen; Lin, Juan; Ye, Xiuyun (Frontiers in Microbiology, 2017)
Laccases are a family of copper-containing oxidases with important applications in bioremediation and other various industrial and biotechnological areas. There have been over two dozen reviews on laccases since 2010 covering various aspects of this group of versatile enzymes, from their occurrence, biochemical properties and expression to immobilization and applications. This review is not intended to be all-encompassing; instead, we highlighted some of the latest developments in basic and applied laccase research with an emphasis on laccase-mediated bioremediation of pharmaceuticals, especially antibiotics. Pharmaceuticals are a broad class of emerging organic contaminants that are recalcitrant and prevalent. The recent surge in the relevant literature justifies a short review on the topic. Since low laccase yields in natural and genetically modified hosts constitute a bottleneck to industrial-scale applications, we also accentuated a genus of laccase-producing white-rot fungi, Cerrena, and included a discussion with regards to regulation of laccase expression.